(3bUjOI aj aVd GdML hGdefGScs - (3CHh YHO Gddg Hf CHj HcQ GdHZOGOjs ((3YHO dGdg Hf YHO GdhGMO Hf YHO GddWja Hf TYjH Hf YHO GdSdGe s)
(3ChdgG (B:s
(3CjG YPHGJ GdHGd ef Cjef GdMei QYi Gddg YjTkG ai QHGc bWYfGg s
(3BNQgG (B:s
(3ahG CSa GdSGQi EPG PcQ GdMei EPG QHY NjQ GdeQSdjf JNWGg JeJ GdefXheI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHI s
(3HgG Jedc HGSe YHO Gddg Hf YHO GdhGMO Hf YHO GddWja Hf TYjH Hf YHO GdSdGe hjQLY JGQjNgG Edi SfI (B1294 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs